Socioeconomic and investment profile of environment control in a swine integration system - Beker, Fabricio Murilo; França, Ismael [UNESP]; Tomas, Júlia; Siqueira, Helloa Alaide; Lima, Gustavo Freire Resende; Rizzoto, Guilherme [UNESP]; Peripolli, Vanessa; Bianchi, Ivan (Revista Brasileira de Zootecnia, 2022)
The objective of this study was to characterize and understand the investment profile towards technologies for control and automation of climate control on swine farms, focused on integrated producers on the same integration system. A structured questionnaire including open, dichotomic, or multiple-choice questions was responded by 190 integrated producers classified as nursery (28,300 swines), wean-to-finish (WTF; 144,388 swines), or finishing unit (FU; 164,185 swines) farms. Data were described and categorized according to the type of integrated producer (nursery, WTF, and FU) and income history during a 24-month interval. The most predominant farmer profile was of a 44.5-year-old man, with incomplete secondary education. Furthermore, the majority of the farms had family-based labor with an average area of 43.6±65.5 ha and ~2.4 economic activities developed. Overall, a reduced labor availability was observed, although the integrated producers declared to be satisfied with the activities. Interestingly, integrated producers with a better income history declared a longer working (high = 37; average = 31; regular = 31; low = 28 min). The investment profile in automation technologies is conservative; however, potential improvements in pig performance were the most popular justification for potential investments. Furthermore, high costs, knowledge in technologies, interest rates, and quality of the available material are the limiting factors for investing in environment control. A total of 74% of the integrated producers considered the activity as economically profitable. Lastly, the uptake of environmental control technologies is strongly associated with the average income received by farmers.
Keywords: automation technology; pig farming innovation; pig production; smart farming; structured survey